EGFR Signaling Is Required for Maintaining Adult Cartilage Homeostasis and Attenuating Osteoarthritis Progression. (9th March 2022) - Wei, Yulong; Ma, Xiaoyuan; Sun, Hao; Gui, Tao; Li, Jun; Yao, Lutian; Zhong, Leilei; Yu, Wei; Han, Biao; Nelson, Charles L.; Han, Lin; Beier, Frank; et al.
ABSTRACT: The uppermost superficial zone of articular cartilage is the first line of defense against the initiation of osteoarthritis (OA). We previously used Col2‐Cre to demonstrate that epidermal growth factor receptor (EGFR), a tyrosine kinase receptor, plays an essential role in maintaining superficial chondrocytes during articular cartilage development. Here, we showed that EGFR activity in the articular cartilage decreased as mice age. In mouse and human OA samples, EGFR activity was initially reduced at the superficial layer and then resurged in cell clusters within the middle and deep zone in late OA. To investigate the role of EGFR signaling in postnatal and adult cartilage, we constructed an inducible mouse model with cartilage‐specific EGFR inactivation ( Aggrecan‐CreER Egfr Wa5/flox, Egfr iCKO ). EdU incorporation revealed that postnatal Egfr iCKO mice contained fewer slow‐cycling cells than controls. EGFR deficiency induced at 3 months of age reduced cartilage thickness and diminished superficial chondrocytes, in parallel to alterations in lubricin production, cell proliferation, and survival. Furthermore, male Egfr iCKO mice developed much more severe OA phenotypes, including cartilage erosion, subchondral bone plate thickening, cartilage degeneration at the lateral site, and mechanical allodynia, after receiving destabilization of the medial meniscus (DMM) surgery. Similar OA phenotypes were also observed in female iCKO mice. Moreover, tamoxifen injections of iCKO mice at 1 month post‐surgery accelerated OA development 2 months later. In summary, our data demonstrated that chondrogenic EGFR signaling maintains postnatal slow‐cycling cells and plays a critical role in adult cartilage homeostasis and OA progression. © 2022 American Society for Bone and Mineral Research (ASBMR).